Rural tourism destination competitiveness : the moderating impact of community support - Chin, Chee Hua (University Malaysia Sarawak, UNIMAS, 2015)
Tourism is one of the largest economic sectors in most of the countries, and contributes to the economic growth in Malaysia. It is also a highly competitive environment, which forces tourism players to provide better visitor services in order to stay competitive. In rural tourism, a growing niche in the tourism market, multiple components of environmental constructs, such as natural resources, cultural heritage, infrastructure, environmental quality and environmental conservation, play a crucial role in contributing to the sustainability and competitiveness of rural tourism destinations. Furthermore, the attitudes of local communities toward tourism development influence its success or failure. Hence, this study examined the impact of multi-environment components on development of tourism destination competitiveness from a local community perspective. In addition, community support was adopted as moderator variable to examine the relationship among the constructs. A total of 300 questionnaires were distributed to local communities from three rural tourism destinations, Bario Kelabit Highland, Annah Rais Bidayuh Longhouse, and Bako National Park, with 249 usable sets of data returned. Data analysis was performed using SPSS Version 21.0 and SmartPLS 2.0 (M3) to assess the developed model, based on path modelling and then bootstrapping. The findings of this study showed that 7 direct relationship hypotheses and 3 moderated relationships were supported. The results revealed that the multi-environmental constructs such as environmental conservation, environmental education, tourism infrastructure, carrying capacity, climate change, quality of environment, and natural resources have a significant positive impact on destination competitiveness from a local community perspective. Interestingly, community support was found to moderate the relationships between tourism infrastructure, relaxation, and climate change towards destination competitiveness. This study enhances both scholars’ and practitioners’ understanding of the impact of multi-environmental constructs on destination competitiveness and the influence of community support in linking the relationship among the constructs. This study provides a basis for future researchers interested in the field of rural tourism studies to further investigate the relationship among the constructs. The findings of this study also provide valuable information to tourism stakeholders and policy planners about the importance of environmental attributes and community support towards the development of tourism destination competitiveness, particularly in the context of rural tourism. The chapters of this study are organised in the following sequence. Chapter 1 presents the introduction, Malaysian scenario, problem statement and purpose of the study. Chapter 2 reviews the past literature on environmental components and destination competitiveness from rural tourism context. Chapter 3 demonstrates the research methodology, sampling, the measurement instrument to be used, the statistical analysis, and the hypothesis of the study. Chapter 4 summarises and presents the output from the statistical analysis. Chapter 5 discusses the findings, and Chapter 6 presents limitations and implications of this study as well as suggestions for future research.